Đề xuất quy trình dạy học chủ đề “Thơ lục bát” (Ngữ văn lớp 6) theo hướng tích hợp nội dung “Giáo dục địa phương thành phố Hà Nội” - Lê, Thị Hiền (Tạp chí Giáo dục, 2025)
In the context of educational reform oriented toward competence development, thematic and integrated teaching has become an essential trend, aiming to enhance practicality and contribute to the formation of students’ comprehensive qualities and competencies. However, at the lower secondary level - particularly in Grade 6 Literature, with the “Lục bátpoetry” form, which holds deep national cultural values - there remains a lack of a systematic and concrete instructional procedure for effectively integrating local educational content. Based on an adaptation of both domestic and international integration models, this article proposes a six-step teaching procedure for the Grade 6 topic “Lục bátPoetry” integrating the local educational content of Hanoi. The procedure includes: (1) Researching the theoretical foundation; (2) Defining learning objectives; (3) Designing content and structure; (4) Developing teaching and learning activities; (5) Assessment; (6) Feedback and refinement. The entire process is built on a competence-based approach, emphasizing the subject’s specific characteristics, ensuring scientific, pedagogical, and practical validity. It contributes to developing students’ language and literary competencies while nurturing their love for their homeland and awareness of preserving local cultural identity.